Effects of rosuvastatin on post-thrombotic syndrome following deep vein thrombosis: a randomized clinical trial - Fayadh, Noor Abbas Hummadi; Khaleel Al-Anbari, Abbas Jaafar; Makki Al-Hindy, Hayder Abdul-Amir (Pharmakeftiki, 2025)
This study evaluates the effectiveness of rosuvastatin as an adjunct to standard anticoagulant therapy in reducing the incidence of post-thrombotic syndrome (PTS) in patients with deep vein thrombosis (DVT) treated at the Al-Imamain Al-Kadhimain Medical City between October 2022 and September 2024. A total of 465 patients were randomized into two groups: a control group receiving standard anticoagulants (warfarin or rivaroxaban) and an intervention group receiving the same anticoagulants with the addition of rosuvastatin. Over the subsequent three months, the authors assessed the development of PTS and measured the serum concentrations of D-dimer and C-reactive protein (CRP). The occurrence of PTS was found to be significantly lower in the rosuvastatin group compared to the control group (p=0.021), with no severe adverse events reported. Furthermore, the intervention group exhibited marked reductions in CRP and D-dimer levels, suggesting that rosuvastatin may contribute to improved clinical outcomes in the management of DVT. These findings support the incorporation of rosuvastatin into conventional anticoagulant regimens as a means of mitigating PTS risk and enhancing overall recovery. The study underscores the value of adjunct therapies in reducing long-term complications associated with venous thromboembolism.